Données préliminaires concernant les formes de l’azote minéral dans les eaux de mer du littoral Roumain - Dorogan, Liliana; Popa, Lucia; Voinescu, Iulia (Cercetări Marine - Recherches Marines, 2026)
This paper presents the interdependence of the mineral nitrogen forms from the Romanian offshore waters, in hydrobiologic conditions to the period of the December 1979 — November 1981